The plant-associated Pantoea spp. as biocontrol agents: Mechanisms and diversity of bacteria-produced metabolites as a prospective tool for plant protection - Simon Duchateau; Jérôme Crouzet; Stéphan Dorey; Aziz Aziz (Biological Control)
Bacteria from the Pantoea genus are regularly found to interact with a variety of plants, as pathogens or as beneficial bacteria, depending on the strain and the host plant. Despite increasing interest in this bacterial genus, the mechanisms by which it interacts with pathogens and host plants remain to be deciphered. This review addresses the current knowledge about the various types of interactions and metabolic traits of Pantoea spp. in protecting plants against pathogens, from direct antagonism to stimulation of plant innate immunity. The biocontrol capacity of Pantoea species mainly relies on the production of a diversity of natural metabolites. In this review, we also discuss the identity and the potential role of these metabolites in Pantoea-driven plant protection.